ISU STRATEGIS TERKAIT PENGEMBANGAN USAHA MIKRO KECIL MENENGAH PADA KAWASAN BOROBUDUR SEBAGAI DESTINASI SUPER PRIORITAS - Brian, Reagan; Rahmanita, Myrza (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023)DO - 10.24843/IPTA.2023.v11.i01.p10, 2023)
Small and Medium-Sized Enterprises (SMEs) or Usaha Mikro Kecil Menengah (UMKM) have significant role in tourism sector during COVID-19 Pandemic. SMEs was the main income generator for the tourism sector due to the limited movement of people, so there are no tourists in the destinations. Despite the fact, SMEs in many tourists destinations in Indonesia are still facing many issues. There are also limited study that identified the issues facing by the SMEs in tourist destinations. This study try to identify the strategic issues facing by the SMEs. This study was conducted using qualitative approach and data were obtained from the results of Focus Group Discussions (FGD), interviews, and observations.  This study used the Nvivo analysis tool version 12 to process the data. The processed data is qualitative data obtained from questionnaires and FGD results. Qualitative data processing methods carried out are data reduction, data presentation, and drawing conclusions. The results shows that the issuses are experiencing not only by the SMEs but also by another industry player related. The SMEs are experiencing strategic issues in resources, both capital and human resouces. There are assistance program by the government regarding this issues, but the effectiveness of the programs are still low as feel by the SMEs.